AI for immunology - Catania, Louis J. (Milton Park, Abingdon, Oxon ; Boca Raton, FL : CRC Press, 2021)
The bioscience of immunology has given us a better understanding of human health and disease. Artificial intelligence (AI) has elevated that understanding and its applications in immunology to new levels. Together, AI for immunology is an advancing horizon in health care, disease diagnosis, and prevention. From the simple cold to the most advanced autoimmune disorders and now pandemics, AI for immunology is unlocking the causes and cures. Key features: A highly accessible and wide-ranging short introduction to AI for immunology Includes a chapter on COVID-19 and pandemics Includes scientific and clinical considerations, as well as immune and autoimmune diseases
OCLC-licensed vendor bibliographic record.
Keywords: Immunoinformatics; SCIENCE / Biotechnology; MEDICAL / Biotechnology; SCIENCE / Life Sciences / Biology / General